Health impacts and environmental footprints of diets that meet the Eatwell Guide recommendations: analyses of multiple UK studies - Scheelbeek, P; Green, R; Papier, K; Knuppel, A; Alae-Carew, C; Balkwill, A; Key, TJ; Beral, V; Dangour, AD (BMJ Publishing Group, 2020)
Objectives To assess the health impacts and environmental consequences of adherence to national dietary recommendations (the Eatwell Guide (EWG)) in the UK. Design and setting A secondary analysis of multiple observational studies in the UK. Participants Adults from the European Prospective Investigation into Cancer - Oxford(EPIC-Oxford), UK Biobank and Million Women Study, and adults and children aged 5 and over from the National Diet and Nutrition Survey (NDNS). Primary and secondary outcome measures risk of total mortality from Cox proportional hazards regression models, total greenhouse gas emissions (GHGe) and blue water footprint (WF) associated with ‘very low’ (0–2 recommendations), ‘low’ (3–4 recommendations) or ‘intermediate-to-high’ (5–9 recommendations) adherence to EWG recommendations. Results Less than 0.1% of the NDNS sample adhere to all nine EWG recommendations and 30.6% adhere to at least five recommendations. Compared with ‘very low’ adherence to EWG recommendations, ‘intermediate-to-high adherence’ was associated with a reduced risk of mortality (risk ratio (RR): 0.93; 99% CI: 0.90 to 0.97) and −1.6 kg CO2eq/day (95% CI: −1.5 to −1.8), or 30% lower dietary GHGe. Dietary WFs were similar across EWG adherence groups. Of the individual Eatwell guidelines, adherence to the recommendation on fruit and vegetable consumption was associated with the largest reduction in total mortality risk: an RR of 0.90 (99% CI: 0.88 to 0.93). Increased adherence to the recommendation on red and processed meat consumption was associated with the largest decrease in environmental footprints (−1.48 kg CO2eq/day, 95% CI: −1.79 to 1.18 for GHGe and −22.5 L/day, 95% CI: −22.7 to 22.3 for blue WF). Conclusions The health and environmental benefits of greater adherence to EWG recommendations support increased government efforts to encourage improved diets in the UK that are essential for the health of people and the planet in the Anthropocene.